“All I miss is soul”: Negotiating Legitimacy, Identity, and Taste in the Age of AI Music - Hsu,En-Jia (2025)
This thesis investigates how AI-generated music challenges traditional systems of cultural legitimacy, identity, and musical taste. Drawing on Bourdieu’s theory of cultural fields and symbolic capital, and supplemented by Simon Frith’s insights into authenticity and identity performance, the study examines how emerging technologies reconfigure creative authority within platform-driven environments. While technological innovation has long shaped music production, the rise of generative AI tools such as Suno and AIVA signals a deeper shift – transforming not only how music is made, but also what counts as music, who qualifies as a creator, and how artistic value is assigned. Reddit serves as the site of inquiry, offering a space where users confront AI-generated music through emotionally charged discourse. Using qualitative text analysis of posts from multiple subreddits, the study explores how users debate authorship, authenticity, and legitimacy in the age of automation. These discussions reveal symbolic struggles over the redefinition of “real music,” where prompt fluency and curatorial agency increasingly supplement traditional markers like instrumental skill and genre literacy. Musical taste, in turn, emerges as a performative signal – strategically enacted through discourse, emotional stance, and algorithmic fluency. The findings show that AI-generated music is not merely a technical development but a cultural provocation. It unsettles boundaries between human and machine, creation and curation, expression and automation. Human-made music takes on new meaning as a symbolic act of intentionality, friction, and distinction. At the same time, legitimacy is no longer conferred solely by institutions but negotiated through platform infrastructures and digital visibility. As generative technologies expand creative access, they also raise tensions about authorship, automation, and the reorganization of symbolic capital. Ultimately, this thesis argues that cultural authority is not disappearing – but being redistributed, remixed through new struggles over value in algorithmically shaped cultural fields.
Keywords: AI-generated music; cultural legitimacy; authorship; taste; identity; Bourdieu; Reddit; algorithmic culture; symbolic capital